Pengaruh Kondisi Lingkungan dan Perilaku terhadap Kejadian Penyakit Demam Berdarah Dengue: Tinjauan Pustaka - Toru, Veronika; Pekabanda, Kartini; Mila, Antonetha R H; Radandima, Ester; Noviana, Ineke (JURNAL KESEHATAN PRIMER, 2022)
Background: Dengue Hemorrhagic Fever (DHF) is a significant health problem in Indonesia, especially in endemic areas. Even though public knowledge about dengue fever is adequate, the implementation of preventive behavior such as 3M Plus is still low. Environmental factors such as rainfall, temperature, humidity and population density also play a role in increasing the risk of spreading this disease. Objective: This study aims to review literature related to environmental factors and community preventive behavior that contribute to the incidence of dengue fever, as well as provide recommendations for interventions for more effective prevention. Method: This research uses a literature review study method by collecting data from scientific journals available on Google Scholar, PubMed, and Elsevier. This study identifies the relationship between environmental factors and 3M Plus behavior on the incidence of dengue fever, and analyzes relevant findings to develop better prevention strategies. Results: There is a significant relationship between environmental factors such as rainfall, temperature, humidity and population density with an increase in the incidence of dengue fever. Even though the public knows the dangers of dengue fever, many still rely on fogging and do not apply 3M Plus consistently. Behavioral factors such as lack of larval inspection and environmental cleanliness also have a big influence.